1997
DOI: 10.1149/1.1837828
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolyzed Polysiloxanes for Use as Anode Materials in Lithium‐Ion Batteries

Abstract: More than sixty siloxane polymers containing various organofunctional siloxane units were synthesized. The synthesized siloxane polymers were pyrolyzed in inert gas at 1000°C. Chemical analysis showed that the products of pyrolysis were distributed over a well‐defined region in the Si‐C‐O Gibbs phase diagram. The electrochemical and structural properties of these materials were measured using coin‐type test cells and x‐ray powder diffraction, respectively. The most interesting materials are found near the line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
1
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(83 citation statements)
references
References 0 publications
4
77
1
1
Order By: Relevance
“…The same evidence can be found in a review by Skundin and co-authors, published in Uspekhi Khimii journal (Russian Chemical Review) (390 references) [93]. The fi rst experimental studies of the processes of lithium introduction into anodes containing silicon nanoparticles were reported in [98][99][100][101][102][103][104][105].…”
Section: E MVsupporting
confidence: 56%
“…The same evidence can be found in a review by Skundin and co-authors, published in Uspekhi Khimii journal (Russian Chemical Review) (390 references) [93]. The fi rst experimental studies of the processes of lithium introduction into anodes containing silicon nanoparticles were reported in [98][99][100][101][102][103][104][105].…”
Section: E MVsupporting
confidence: 56%
“…Usually "soft" carbons consist of graphene layers which can develop graphitic structures with increasing temperature. 6 In numerous studies related to disordered carbons, Dahn et al [7][8][9][10][11][12][13][14]25,26 have demonstrated that in both cases, for soft and hard carbons, the reversible capacity reaches its minimum for heat-treatments of the materials at about 1700 • C. However the reversible capacity of hard carbons thermolyzed at T < 1700 • C should be higher than that observed for our SiCN samples 1, 2 and 3. This result indicates the presence of soft disordered carbons in our investigated materials.…”
Section: Electrochemical Studies: First Lithium Intercalation/extractionmentioning
confidence: 49%
“…7 Lithium intercalation in some disordered carbons derived from various precursors, e.g. sucrose, 8,9 petroleum coke, 10 pitch-polysilanes blends, 11,12 siloxanes, [13][14][15][16][17][18] and silazanes [19][20][21][22] has been studied in the presence of conductive additives such as acetylene black powder. 22 It was demonstrated that despite the quite high irreversible capacity observed during first intercalation/deintercalation, the disordered carbons are perspective materials for negative electrodes in lithium-ion batteries because of their relatively high reversible capacity, stability in cycling, low price and availability.…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, these performance differences reveal that the microstructures of our TVS- doped PMAN carbons are still somewhat different from those of of the pitch-polysiloxane blends studied in Ref. 6 which were prepared at a much higher temperature than our PMAN carbons. The precursor pyrolysis temperature can have profound effects on the resulting microstructure and chemistry of the resulting carbons.…”
Section: Discussionmentioning
confidence: 68%